2020
DOI: 10.1186/s12903-020-01209-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of adjunctive azithromycin on microbiological and clinical outcomes in periodontitis patients: 6-month results of randomized controlled clinical trial

Abstract: Background: Our aim was to determine if azithromycin therapy, as an adjunct to scaling and root planing (SRP), decreases the number of pathobiontic subgingival plaque species and sites demonstrating pocket depth (PD) ≥ 5 mm and bleeding on probing (BOP) 6 months post-treatment. Methods: In a double-blind randomized parallel-arm placebo-controlled trial, 40 patients received nonsurgical periodontal treatment in two sessions within 7 days. Patients then received systemic antibiotic therapy (n = 20, azithromycin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 44 publications
2
21
0
Order By: Relevance
“…In this study, percentage of residual pockets significantly decreased at 3 months compared with baseline in all treatment strategies and maintained at 6 months. These findings were in accordance with previous studies 23,24,26,60 . Furthermore, the percentage of residual pockets was significantly lower after FMD than FM‐SRP or Q‐SRP at 3 months, but only Q‐SRP at 6 months.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, percentage of residual pockets significantly decreased at 3 months compared with baseline in all treatment strategies and maintained at 6 months. These findings were in accordance with previous studies 23,24,26,60 . Furthermore, the percentage of residual pockets was significantly lower after FMD than FM‐SRP or Q‐SRP at 3 months, but only Q‐SRP at 6 months.…”
Section: Discussionsupporting
confidence: 93%
“…These findings were in accordance with previous studies. 23,24,26,60 Furthermore, the percentage of residual pockets was significantly lower after FMD than FM-SRP or Q-SRP at 3 months, but only Q-SRP at 6 months. To date, there are no other studies available to enable comparisons between the re- Periodontal disease activity is regulated by complex interactions between the host immune system and periodontal pathogens.…”
Section: Discussionmentioning
confidence: 88%
“…The results of current study showed that by comparing clinical parameters demonstrated that there was an improvement in all clinical parameters (PD, GI, PI and CAL) in all groups with no significant difference between groups after a period of 3 months from NSPT. These results was in agreement with several studies that showed either NSPT alone or in conjunction with adjunctive therapy could improve the clinical outcomes with controlled TⅡDM periodontitis patients (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) .Group III who received azithromycin showed the highest improvement in GI. These results could be explained by the fact that SDD could enhance the results of a number of mechanical nonsurgical interventions by inhibition of MMPs which is involved in periodontal tissue destruction (31) .…”
Section: Discussionsupporting
confidence: 91%
“…These studies were conducted in Asia [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], South America [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ], Europe [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 ], and Australia [ 81 , 82 ]. They were mostly single-centered [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ...…”
Section: Resultsmentioning
confidence: 99%